Pengaruh Pengelolaan Waktu dan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Pendidikan Ekonomi di Universitas PGRI Wiranegara - Arum Masyitoh; Sugeng Pradikto (Jurnal Manajemen Riset Inovasi, 2025)
This research aims to evaluate the impact of time management and activeness in organizations on the academic achievement of Economics Education students at PGRI Wiranegara University. Using a quantitative approach, data was collected through questionnaires given to 60 students and analyzed using the multiple linear regression method. The results of the analysis show that there is a significant positive relationship between good time management and active participation in organizations on student academic achievement. These findings emphasize the importance of personal discipline and extracurricular activities in supporting academic success.